P869 Mucosa-associated dysbiosis in inflammatory bowel disease. (16th January 2018) - Andoh, A; Inoue, R; Naito, Y
Abstract: Background: The mucosa-associated gut microbiota directly modulates epithelial and mucosal function. In this study, we investigated the mucosa-associated microbial community in patients with inflammatory bowel disease (IBD) using endoscopic brush samples. Methods: This study was approved by the ethics committee of the Shiga University of Medical Science (permission No. 28-111). Samples were obtained by gentle brushing of mucosal surfaces while avoiding bleeding using cytology brushes (COOK® CCB-7-240-3-S, Bloomington, IN). In total, 174 mucus samples from 26 ulcerative colitis (UC), 43 Crohn's disease (CD) and 14 non-IBD controls were obtained by gentle brushing of mucosal surfaces using endoscopic cytology brushes. The gut microbiome was analysed using 16S rRNA gene sequencing. Results: There were no significant differences in the microbial structure between different anatomical sites (the ileum, cecum and sigmoid colon) within the individual. There was a significant difference in the microbial structure between CD, UC and non-IBD controls. The difference between CD and non-IBD controls was more remarkable than that between UC patients and non-IBD controls. alpha-diversity was significantly lower in UC and CD patients compared with non-IBD controls. When comparing CD patients with non-IBD controls, the phylum Proteobacteria was significantly increased, and the phyla Firmicutes and Bacteroidetes were significantly reduced. These included a significant increase of the genera Escherichia, Ruminococcus ( R. gnavus ), Cetobacterium, Actinobacillus, and Enterococcus and a significant decrease of the genera Faecalibacterium, Coprococcus, Prevotella, Roseburia. Comparison between CD and UC patients revealed that the genera Escherichia, Ruminococcus ( R. gnavus ), Clostridium, Cetobacterium, Peptostreptococcus were more abundant in CD patients and that the genera Faecalibacterium, Blautia, Bifidobacterium, Roseburia, Citrobacter were more abundant in UC patients. Conclusions: Our novel findings are as follows: (a) inter-individual uniformity of the gut microbial structure at different anatomical sites of the colon and ileum, (b) no difference in the microbial structure between inflamed and non-inflamed mucosa, (c) mucosa-associated dysbiosis is more evident in CD patients than UC patients. There is a possibility that collection methods of mucus samples such as biopsy or brushing might strongly affect the results of 16S rDNA sequencing. A comparative study of methods of sample collection should be considered in the future.